1997
DOI: 10.1097/00001756-199707280-00012
|View full text |Cite
|
Sign up to set email alerts
|

Enkephalinergic nerve terminals target inhibitory interneurons in the rat hippocampus

Abstract: Using correlated light and electron microscopic preembedding enkephalin immunocytochemistry combined with post-embedding GABA immunogold staining, we found morphological evidence of a direct connection between the enkephalinergic and GABAergic systems in the rat hippocampus. Enkephalin-immunoreactive boutons were found to be presynaptic to GABA-immunoreactive postsynaptic profiles, establishing type 2 symmetrical synapses on GABA-positive cell bodies and dendritic shafts in strata radiatum and lacunosum molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…The present results demonstrated that the Enk-IR boutons exclusively formed symmetric contacts, and always on GABAergic postsynaptic structures. This is in contrast with an earlier report about the synapses formed by leu-Enk-IR boutons in the rat CA1 region, where both pyramidal cells and interneurons were found among the postsynaptic elements (Füzesi et al, 1997). This difference may be due to the possibility that the leu-Enk antiserum of Füzesi et al (1997) visualizes boutons of both extrinsic and local origin.…”
Section: Enk-ir Axons In the Ca1 Region Innervate Exclusively Gabaergcontrasting
confidence: 99%
See 2 more Smart Citations
“…The present results demonstrated that the Enk-IR boutons exclusively formed symmetric contacts, and always on GABAergic postsynaptic structures. This is in contrast with an earlier report about the synapses formed by leu-Enk-IR boutons in the rat CA1 region, where both pyramidal cells and interneurons were found among the postsynaptic elements (Füzesi et al, 1997). This difference may be due to the possibility that the leu-Enk antiserum of Füzesi et al (1997) visualizes boutons of both extrinsic and local origin.…”
Section: Enk-ir Axons In the Ca1 Region Innervate Exclusively Gabaergcontrasting
confidence: 99%
“…1997). This difference may be due to the possibility that the leu‐Enk antiserum of Füzesi et al . (1997) visualizes boutons of both extrinsic and local origin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to the sources of heterogeneity described above, there is good evidence that different groups of interneurons are selectively innervated by distinct neurotransmitter-containing afferents (Freund and Antal, 1988;Freund et al, 1990;Fuzesi et al, 1997). Furthermore, different interneurons express distinct sets of neurotransmitter receptors (McBain and Dingledine, 1993;McBain et al, 1994;Bergles et al, 1996;McMahon and Kauer, 1997;Miller et al, 1997;Morales and Bloom, 1997;Frazier et al, 1998;Svoboda and Lupica, 1998), suggesting further segregation of function.…”
mentioning
confidence: 97%